Meta-evaluation of a participatory process in the strengthening of municipal management - Cristiane Andrea Locatelli de Almeida; Oswaldo Yoshimi Tanaka (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE To evaluate, with a focus on participation, an evaluation process developed by municipal managers and administrators of a health region in the state of São Paulo, considering the need for theoretical reflection on participatory health practices in the Brazilian context. METHODS Qualitative research that used the framework developed by Daigneault and Jacob (2009) to analyze the empirical material, encompassing three dimensions of participation: control of the evaluation process, diversity of participants, and extent of their involvement. We highlighted decisions or contextual aspects that deepened or limited the participatory option in the process under study. RESULTS We identified the presence and important performance of stakeholders who are "not specialists in evaluation", through participation both in the direction of the evaluation process and in its distinct stages. The formed group started from their own annoyances added to the need for information and reflection to define the subject and scope of the evaluation; the use of the process planned by them guided the definition of the data to be collected and the format of result dissemination; the empirical material analysis was undertaken jointly by the participants. Regarding the third dimension, a limitation was identified regarding the diversity of actors involved due to the prioritization of the possibility of in-depth work with a fixed group of managers. CONCLUSIONS It is stated that there is no "ideal participation model" for evaluations. In certain contexts and structures, real opportunities for participation - even if they seem fragile at first sight - should be leveraged, and that requires flexibility and critical reflection on the part of those responsible for the evaluation processes to undertake the necessary adjustments.